Implementasi Teori Sistem Terbuka Dalam Pengelolaan Sumber Daya Manusia Rumah Sakit - Purwadhi, Purwadhi; Widjaja, Yani Restiani; Setyagraha, Javan Agustian; Umchudloh, Umchudloh (Jurnal sosial dan sains, 2025)
This study aims to analyze the implementation of open systems theory in the management of human resources (HR) within a hospital setting. As complex and dynamic healthcare service organizations, hospitals are required to adapt to external changes such as regulations, technology, and patient expectations. The open systems approach introduced by Katz and Kahn (1978) emphasizes the importance of input, process, output, feedback, and environmental adaptation for organizational sustainability. This research employs a qualitative approach through a case study at Hospital X. Data were collected through in-depth interviews, participatory observation, and document analysis, and were analyzed using NVivo software to identify dominant themes. The findings reveal that all elements of the open systems model have been gradually implemented, indicated by demand-based recruitment, cross-unit training, periodic performance evaluations, and the hospital's ability to respond to external changes such as the pandemic and digital transformation. Thematic analysis shows that the five elements interact to form an adaptive and responsive HR management ecosystem. These findings reinforce the argument that a managerial system based on open systems theory enhances productivity, inter-unit coordination, and service quality. This study contributes theoretically to strengthening organizational systems in the healthcare sector and offers practical recommendations for hospital management to optimize HR processes through data, technology, and continuous evaluation.